Draft Sixth Five Year Plan 1980-85 and Annual Plan 1981-82 Volume II State Planning Board Trivandrum - Planning Commission (Planning Commission, 1981)
Outlay and Expenditure Scheme-wise Selected Targets and Achievements Minimum Needs Programme—Outlay and Expenditure Minimum Needs Programme—Targets and Physical Achievements Centrally Sponsored Schemes—Outlays Major and Medium Irrigation Projects—Outlays and Expenditure Major and Medium Irrigation Projects—Phasing of Outlay Major and Medium Irrigation Projects—Benefits Targets and Achievements Flood Control Drainage Anti-Sea Erosion and Water Logging Projects—Outlays and Expenditure.
State Planning Board, Trivandrum